Higher Practice Intensity Is Associated with Higher Quality of Care but More Avoidable Admissions for Medicare Beneficiaries - Landon, Bruce E. (Springer US, 2014)
BACKGROUND: The relationship between practice intensity and the quality and outcomes of care has not been studied. OBJECTIVE: To examine the relationship between primary care physicians’ costliness both for defined episodes of care and for defined patients and the quality and outcomes of care delivered to Medicare beneficiaries. STUDY DESIGN: Cross sectional analysis of physician survey data linked to Medicare claims. Physician costliness measures were calculated by comparing the episode specific and overall costs of care for their patients with the care delivered by other physicians. PARTICIPANTS: We studied physicians participating in the 2004–2005 Community Tracking Study Physician Survey linked with administrative claims from the Medicare program for the years 2004–2006. MAIN MEASURES: Proportion of eligible beneficiaries receiving each of seven preventive services and rates of preventable admissions for acute and chronic conditions. KEY RESULTS: The 2,211 primary care physician respondents included 937 internists and 1,274 family or general physicians who were linked to more than 250,000 Medicare enrollees. Patients treated by more costly physicians (whether measured by the overall costliness index or the episode-level index) were more likely to receive recommended preventive services, but were also more likely to experience preventable admissions. For instance, physicians in the lowest quartile of costliness performed appropriate monitoring for hemoglobin A1C for diabetics 72.8 % of the time, as compared with 81.9 % for physicians in the highest quartile of costliness (p < 0.01). In contrast, patients treated by the physicians in the lowest quartile of episode costliness were admitted at a rate of 1.8/100 for both acute and chronic Prevention Quality Indicators (PQIs), as compared with 2.9/100 for both acute and chronic PQIs for those treated by physicians in the highest quartile of costliness (p < 0.001). CONCLUSIONS: Physician practice patterns are associated with the quality of preventive services delivered to Medicare patients. Ongoing efforts to influence physician practice patterns may have differential effects on different aspects of quality.